KARAKTERISTIK PEMBAGIAN WARIS ADAT JAWA - Sri Astutik (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2019)
The distribution of inheritance among Javanese indigenous people, has its own characteristics. Although in general there are rules that have become a custom that applies from generation to generation, but in practice there are some variations in the implementation of inheritance. Submission of assets to his off spring does not have to wait for the death of the testator, but can be carried out while the testator is still alive. There are also those who share the inheritance after the testator dies and or the heir has finished his life (1000 days). In Javanese traditional inheritance law there are also known heirs, namely heirs who replace the main heirs, if he dies first. Every child has the right to become an heir, but the portion may differ depending on the habits in the family environment. There are heirs who get the same portion, some who get 2 for men and : 1 for women, and there are also certain heirs getting more shares.